"Indicadores productivos y socio-económicos del cultivo de cacao en la población de Guantupí, cantón Valencia. Propuesta alternativa ecológica - Córdova Maldonado, Hugo Rene (2009)
The research entitled “PRODUCTIVE INDICATORS AND PARTNER - ECONOMICS OF CACAO CULTIVATION IN THE POPULATION OF GUANTUPÍ, CANTON VALENCIA. ECOLOGICAL ALTERNATIVE PROPOSAL ”presents the analysis of the productive, economic and social indicators, where all the cocoa producers in the Guantupí sector are immersed and that feel affected by production levels and ignorance in organize to achieve common ends has disturbed the farmers of this sector. The study allowed for a thorough analysis to determine weaknesses of the producers in the cocoa production of the Guantupí sector, know the amount of land they cultivated, the number of quintals they produce per hectare, if they have renovated their plantations to obtain higher yields and provide a better quality of life for the family. This research leads to establishing the decisions made by the cocoa producers facing the purpose, that they do not destroy their national cocoa, to renew it and having a potential to produce organic cocoa, commercialize directly locally and for export, the purpose of which is that contribute to improving their economic situation, but taking care of the environment. The results of the investigation allowed to conclude that the producers have lack of knowledge to organize, they do not use the proper procedures nor the appropriate control in the application of products for the fertilization of the land and biological control, do not have access to agricultural technology and systems of environmental management rather contribute to the degeneration of the local landscape ...................................... ....................